Invasive Physiologic Study Across Various Spectrum of Coronary Artery Fistulas with Concomitant Coronary Artery Stenosis - Sembiring, Theresia Sri Rezeki; Mangkuanom, Arwin Saleh; Firman, Doni; Alkatiri, Amir Aziz; Iryuza, Nanda (The Indonesian Heart Association, 2024)
Background: Most CAFs are asymptomatic but it might have serious hemodynamic consequences causing signs and symptoms of myocardial ischemia and heart failure prompting intervention, be it percutaneous or surgical, to manage the hemodynamic burden. Currently, there’s no widely accepted guidelines or consensus to manage patients with CAFs. The decision to undergo intervention is usually based on the presence of symptoms, size and also the anatomic features of the fistula. Case Illustration and Discussion: We presented 5 patients with CAFs undergoing FFR/iFR in our institution. Of all patients, only one showed significant iFR suggesting significant hemodynamic burden, probably due to stealing phenomenon. Number of fistulas varied from 1 – 3 with most fistula arose from left anterior descending and terminated in pulmonary artery. Only one patient underwent RHC showing relatively normal flow ratio supported by normal iFR reading across different coronary artery segments. One patient presented with patent stents in LAD and OM2 despite existing subtotal occlusion in proximal PDA, the other one presented with insignificant stenosis in RCA, and the other two presented with no concomitant stenosis. We underwent no further intervention for 4 patients with normal FFR/iFR reading but we underwent stent implantation for one patient with significant FFR/iFR reading. Upon 1-year-follow up, all patients are currently doing well with no significant complaints of chest pain or dyspnea. Conclusion: Due to limited literature covering the issue of CAFs and coronary artery stenosis, the decision which to intervene first between these two is currently still in the discretion of the attending physician. Whenever possible, further diagnostic work up should always be performed as an objective parameter of hemodynamic burden. FFR/iFR might be considered as one of many modalities to do so. Yet, further well-designed studies are needed to confirm the role of FFR/iFR hoping this modality might someday help in guiding decision-making in patients with CAFs. Keywords: coronary artery fistula; coronary artery stenosis; free fractional reserve (FFR); instantaneous wave free ratio (iFR)